Analisis Pengaruh Pemasaran Online Terhadap Keputusan Pembeli Produk - Metodius Boro Tulit; Marlince Kadobo; Marjelin Putri Ndaparoka; Ningsiana Dappa; Adrianus Soni Wainigha; Petrus Gilfret Putra Bora (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Micro, Small and Medium Enterprises using internet media for online marketing to gain satisfactory market share. Currently, the Internet is very easily accessed by everyone around the world, including UMKM’s businessmen using the Internet as giving and sharing the information for customers about their products offered online. This paper aims to determine how the Effect of Online Marketing Strategy to increase the profit income of SMEs. Respondents in this research are the Owners / Marketing Managers / staff of SMEs in Sumba Barat Daya. The results of this study seeks to answer the hypothesis. H1 is accepted whereas Ho is rejected, stating that online marketing strategy is a positive influence on increasing the Profit Income of SMEs. Keyword: online marketing, strategy, profit, internet, SMEs.